A Foresight Study of Agricultural Robot Implementation in Agriculture Field Malaysia - Nurul Raudah Bariah Sallahuddin,; Norasmiha Mohd Nor, (Research in Management of Technology and Business, 2024)
As we are aware, the agriculture sector is a backbone sector that mainly produces food and goods through small scale cultivation, farming, animal husbandry, fishing and forestry. As farmland narrows and human population is increasing, there needs to be innovation in agriculture or methods to deal with the problem. However, lack of employment and higher average age of workers have contributed to the increase production costs which in turn affect Malaysia’s position in production and export especially the world’s major commodities. This study aims to identify the key drivers behind agricultural robot implementation and explore its potential impact on agriculture field in the future. The target respondent was selected and cover mainly in Johor. The results of the STEEPV analysis indicate that the economical factor is the most critical driver in agricultural robot implementation on future agriculture field, followed by technological, social, values, environmental and political factors. A total of 10 merged key drivers were identified. A total of 382 questionnaires were distributed to the stakeholders in agriculture field in Johor with response rate of 36.39%. The study found that political decisions and policy development and value creations and collaboration have the highest impact and the highest uncertainty. Four scenarios were proposed at the end of the study. The four scenarios were prospering of harmonious innovation, fragmented progress, top-down regulation and policy gridlock.